CHRONIC HEART FAILURE CAUSES OSTEOPATHY OR IS OSTEOPATHY A FACTOR IN DEVELOPMENT OF CHRONIC HEART FAILURE? - Marushchak, Mariya; Krynytska, Inna; Mikolenko, Anna; Andreychyn, Yurii; Bodnar, Yaroslav; CHORNOMYDZ IRYNA (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: As their proportion rises in the aging population, cardiovascular disease and osteoporosis increasingly become significant health problems of the developed world, leading to reduced lifespan and substantial financial burdens, not the least because of complications and comorbidities associated with each disorder. This study investigates bone mineralization in patients with coronary heart disease (CHD) complicated by Stage I chronic heart failure (CHF). Methods: The study group consisted of 41 patients of both sexes with CHF Stage I against the background of CHD that with no severe comorbidities that could have potentially caused changes in bone tissue. Bone mineral density was measured using dual-energy X-ray densitometry of lumbar region of spine and proximal right femur. Results: Structural and functional changes in the bone of the lumbar spine were found in 75.9% of the patients with Stage I CHF caused by CHD. Osteopenia was diagnosed in 64.4% of the patients, while osteosclerotic bone changes were less frequent and found in 11.5% of the patients. 75.8% of the patients had structural and functional changes in the proximal segment of the right femur bone. In men with Stage I CHF against the background of CHD osteopenia was more often diagnosed in the proximal segment of the right femur, while in women it was found in almost equal proportion in the spine and hip. Conclusions: In both sexes with I Stage CHF against the background of CHD were diagnosed changes in bone mineralization, with osteopenia being the prevailing diagnosis. Â